2011
DOI: 10.3109/0886022x.2011.618792
|View full text |Cite
|
Sign up to set email alerts
|

Significant Correlation between Left Ventricular Systolic and Diastolic Dysfunction and Decreased Glomerular Filtration Rate

Abstract: Cardiac dysfunction portends a poor prognosis in renal failure and vice versa. Functional abnormalities of heart in patients with renal insufficiency were frequently noted. The aim of this study is to assess the relationship between left ventricular systolic and diastolic function and renal function in patients with various degrees of renal function. This cross-sectional study included 167 patients from our Outpatient Department of Internal Medicine. Left ventricular systolic and diastolic functions were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Recent clinical studies have shown that serum uric acid can correlate with vascular remodeling [23] and hemodynamic profiles [24] in several patient's populations. Because oxidative stress and inflammation are common in chronic heart failure beyond loss of left ventricular pump function [25, 26], we support a hypothesis that serum uric acid can contribute to influence of inflammatory activation, metabolic disorders, and calcium deposition in plaques and in vasculature [27]. Nevertheless, in the majority of studies there was a significant interrelationship between hyperuricemia (above 7 mg/dL) and cardiovascular outcomes [2830].…”
Section: Discussionsupporting
confidence: 67%
“…Recent clinical studies have shown that serum uric acid can correlate with vascular remodeling [23] and hemodynamic profiles [24] in several patient's populations. Because oxidative stress and inflammation are common in chronic heart failure beyond loss of left ventricular pump function [25, 26], we support a hypothesis that serum uric acid can contribute to influence of inflammatory activation, metabolic disorders, and calcium deposition in plaques and in vasculature [27]. Nevertheless, in the majority of studies there was a significant interrelationship between hyperuricemia (above 7 mg/dL) and cardiovascular outcomes [2830].…”
Section: Discussionsupporting
confidence: 67%
“…In this connection, several studies have investigated the association between CKD measures and cardiac structure and function . However, most of these studies mainly assessed left ventricular (LV) mass or hypertrophy as a parameter of cardiac structure but did not necessarily evaluate measures of LV size.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of SUA have been linked to the body habitus, diuretic use, declining eGFR, as wells as both biochemical (NT-pro-BNP) and hemodynamic (E/Ea and LVEF) markers of CHF by several investigators. 24 , 26 Amin et al reported that even mild elevation of SUA is associated with impaired clinical and hemodynamic profile in patients with systolic CHF and suggested that SUA might be used as a non-invasive indicator of elevated left ventricular filling pressures. 27 Misra et al demonstrated a reverse impact of CHF status (compensation or decompensation) on SUA levels among men with high cardiovascular risk profile.…”
Section: Discussionmentioning
confidence: 99%